Dolichoectasia of the anterior cerebral arteries in an adolescent. - Doran, S E; Deveikis, J P; Chandler, W F (American Journal of Neuroradiology, 1995)
We report a case of bilateral dolichoectasia of the anterior cerebral arteries in a 14-year-old girl as documented by MR imaging and cerebral angiography. Concurrent thickening of the adjacent medial frontal lobes was found, suggesting either a neuronal migrational abnormality or secondary changes attributable to vascular insufficiency.